A new high step-up single switch DC-DC converter with soft switching on all semiconductor elements - vesali, mahmood (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2024)
This paper presents a high step-up DC-DC converter. The converter has a simple structure and without adding any auxiliary switch, soft switching condition is provided in the converter. Due to the fact that any switch is not added to the converter, there is no need to design a new control circuit for this converter and the basic control circuit structure is suitable for this converter. In the proposed converter with minimum number of auxiliary elements soft switching condition provides, which in addition to have a simple structure, reduces losses and increases efficiency. soft switching condition is provided under zero current switching (ZCS) when switch is turned on and under zero voltage switching (ZVS) when the switch is turned off. The voltage stress on the switch is at a lower level than the output voltage of the converter, which the switch can use with low voltage. Also, not much current stress is imposed on the switch, which does not require a very high current switch. The proposed converter has been completely analyzed and in order to prove the theoretical analysis, the converter is implemented at a power of 500 watts and at a full load the efficiency of about 97.2% is obtained.